Desarrollo morfosintáctico según el sexo, la edad y el tipo de gestión educativa en niños de 2 a 3 años de instituciones de educación inicial del distrito de San Juan de Lurigancho - Chauca Girón, Evelyn Eva (2017)
Do you know if the morphosyntactic development is the same in children of different gender, age and school or differs according to these? In the process of language acquisition, there are a number of uncertainties that psycholinguistics, linguistics, psychology and education seek to clarify, in order to improve our knowledge about this situation. Therefore, this thesis tries to describe the morphosyntactic development of children from 2 to 3 years of age and their differences according to sex, age and type of educational management in the district of San Juan de Lurigancho, Lima - Peru. Next, the process, the results and the conclusion of the present investigation will be presented. For this, the Average Length of Morphea Statement (LME) was used as a measurement instrument, since it is an indicator of the morphosyntactic development of a child. In addition, a new proposal of morphosyntactic analysis is presented. In this sense, it was possible to reach the proposed objectives of checking, determining, describing, analyzing and comparing the morphosyntactic development of competent children of the Spanish language. Since the morphemes used in the sample were quantified, which were collected in different spontaneous situations. Likewise, the frequency of use of these morphemes was verified according to sex, age and type of educational management. And the descriptive - correlational method was used. The results will serve to identify linguistic alterations in morphosyntactic development and from this, to propose, in the future, work strategies to improve the performance of children from 2 to 3 years. Also, a morphosyntactic development pattern will be available to guide the planning of future interventions. Finally, we conclude that there are significant differences in morphosyntactic development according to age and type of schooling, but not with respect to sex.